2018
DOI: 10.3390/ijerph15102164
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Sediment and Surface Water of West Dongting Lake and South Dongting Lake: Abundance, Source and Composition

Abstract: Microplastic pollution was investigated in sediment and surface water in West Dongting Lake and South Dongting Lake for the first time. The abundance of microplastics ranged from 616.67 to 2216.67 items/m3 and 716.67 to 2316.67 items/m3 in the lakeshore surface water of West Dongting Lake and South Dongting Lake, respectively. The highest levels of microplastic pollution were found in the lakes’ outlets. In the lake center sites of the West Dongting Lake and South Dongting Lake, the abundance of microplastics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(36 citation statements)
references
References 60 publications
2
32
0
2
Order By: Relevance
“…Fibers were the most dominant shape for both season accounting for 93.04% and 96.69% of the total microplastic observed in lake surface water for winter and rainy season respectively. This result was similar with previous freshwater studies like 20 major lake, China (52.9 -95.6%) (Wang et al, 2017), Taihu Lake, China (48 -84%) (Su et al, 2016), Dongting Lake Chain (12.17 -77.42%) (Jiang et al, 2018), Lake Kallaveshi, Finland (64%) (Uurasjarvi et al, 2020), Lake Naivasha, Kenya (81%) (Migwi et al, 2020)…”
Section: Morphological Of Microplasticsupporting
confidence: 92%
“…Fibers were the most dominant shape for both season accounting for 93.04% and 96.69% of the total microplastic observed in lake surface water for winter and rainy season respectively. This result was similar with previous freshwater studies like 20 major lake, China (52.9 -95.6%) (Wang et al, 2017), Taihu Lake, China (48 -84%) (Su et al, 2016), Dongting Lake Chain (12.17 -77.42%) (Jiang et al, 2018), Lake Kallaveshi, Finland (64%) (Uurasjarvi et al, 2020), Lake Naivasha, Kenya (81%) (Migwi et al, 2020)…”
Section: Morphological Of Microplasticsupporting
confidence: 92%
“…The concern about microplastic pollution in freshwater areas has been booming in recent years [11,12,13,14]. China has the highest plastic production in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of debris, the literature data indicated that the most abundant types of plastic were PE (40%), PS (25%) and PP (Tamar River; Sadri and Thompson, 2014). PS and PET were most common in the surface water and sediment of lakes (Dongting Lakes, Jiang et al, 2018). In urban rivers, microplastic pellets, fibres and fragments were identified as PP, PE and PS (rivers in Illinois, McCormick et al, 2016).…”
Section: Resultsmentioning
confidence: 99%